Functional modulation of gut microbiota in diabetic rats following dietary intervention with pistachio nuts (Pistacia vera L.) - Amalia E. Yanni (Metabolism Open, 2020)
Background: Gut microbiota holds a key-role in numerous biological functions and has emerged as a driving force for the development of diabetes. Diet contributes to gut microbiota diversity and functionality providing a tool for the prevention and management of the disease. The study aimed to investigate the effect of a dietary intervention with pistachio nuts, a rich source of monounsaturated fatty acids, dietary fibers and phytochemicals on gut microbiota composition in the rat model of Type 1 Diabetes. Methods: Male Wistar rats were randomly assigned into four groups: healthy animals which received control diet (CD) or pistachio diet (PD), and diabetic animals which received control diet (DCD) or pistachio diet (DPD) for 4 weeks. Plasma biochemical parameters were determined and histological examination of liver and pancreas was performed at the end of the dietary intervention. Adherent intestinal microbiota populations in jejunum, ileum, caecum and colon were analyzed. Fecal microbiota populations at the beginning and the end of the study were determined by microbiological analysis and 16S rRNA sequencing. Results: Diabetic animals of both groups exhibited high plasma glucose and low insulin concentrations, as well as characteristic pancreatic lesions. Pistachio supplementation significantly increased lactobacilli and bifidobacteria populations in jejunum, ileum and caecum (p < 0.05) and normalized microbial flora in all examined intestinal regions of diabetic animals. After 4 weeks of supplementation, populations of bifidobacteria and lactobacilli were increased in feces of both healthy and diabetic animals, while enterococci levels were decreased (p < 0.05). Next Generation Sequencing of fecal samples revealed increased and decreased counts of Firmicutes and Bacteroidetes, respectively, in healthy animals that received the pistachio diet. Actinobacteria OTUs were higher in diabetic animals and increased over time in the pistachio treated groups, along with increased abundance of Bifidobacterium. Lactobacillus, Turicibacter and Romboutsia populations were elevated in healthy animals administered the pistachio nuts. Of note, relative abundance of Bacteroides was higher in healthy than in diabetic rats (p < 0.05). Conclusion: Dietary pistachio restored normal flora and enhanced the presence of beneficial microbes in the rat model of streptozotocin-induced diabetes.